Aplastic anemia and paroxysmal nocturnal hemoglobinuria in children and adults in two centers of Northern Greece - Gavriilaki, Eleni; Tragiannidis, Athanasios; Papathanasiou, Maria; Besikli, Sotiria; Karvouni, Paraskevi; Douka, Vassiliki; Paphianou, Eleni; Hatzipantelis, Emmanuel; Papaioannou, Giorgos; Athanasiadou, Anastasia; Marvaki, Anastasia; Panteliadou, Alkistis-Kira; et al. (Frontiers in Oncology, 2022)
Bone marrow failure (BMF) syndromes are a group of various hematological diseases with cytopenia as a main common characteristic. Given their rarity and continuous progress in the field, we aim to provide data considering the efficiency and safety of the therapeutic methods, focusing on the treatment of aplastic anemia (AA) and paroxysmal nocturnal hemoglobinuria (PNH). We enrolled consecutive patients diagnosed with BMF in two referral centers of Northern Greece from 2008 to 2020. We studied 43 patients with AA (37 adults and 6 children/adolescents) and 6 with classical PNH. We excluded from further analysis 1 patient with Fanconi anemia Regarding classical PNH, 4 patients have received eculizumab treatment with 1/4 presenting extravascular hemolysis. Among 43 patients with aplastic anemia, PNH clones were detected in 11. Regarding patients that did not receive alloHCT (n=15), 14/15 were treated with ATG and cyclosporine as first line, with the addition of eltrombopag in patients treated after its approval (n=9). With a median follow-up of 16.7 (1.8-56.2) months from diagnosis, 12/14 (85.7%) are alive (4-year OS: 85.1%). AlloHCT was performed in 28 patients. Five patients developed TA-TMA which did not resolve in 3/5 (all with a pre-transplant PNH clone). With the follow-up among survivors reaching 86.3 (6.3-262.4) months, 10-year OS was 56.9%, independently associated with PNH clones after adjusting for age (p=0.024). In conclusion, our real-world experience confirms that novel treatments have revolutionized the field of BMF syndromes. Nevertheless, further studies are needed to personalize algorithms in the era of precision medicine.